Central Extracorporeal Life Support With Left Ventricular Decompression to Berlin Heart Excor: A Reliable "Bridge to Bridge" Strategy in Crash and Burn Patients. Issue 6 (8th November 2016) - Weymann, Alexander; Farag, Mina; Sabashnikov, Anton; Fatullayev, Javid; Zeriouh, Mohamed; Schmack, Bastian; Arif, Rawa; Müller, Florian; Alt, Christina; Raake, Philip; Prakash Patil, Nikhil; Popov, Aron‐Frederik; et al.
Abstract: The aim of this study was to compare patients with severe biventricular heart failure who underwent Berlin Heart Excor implantation with (cardiogenic shock [CS] status) or without the need for preoperative extracorporeal life support (ECLS) as a bridge to long‐term device. A total of 40 consecutive patients with severe biventricular heart failure underwent Berlin Heart Excor implantation with (CS status, n  = 20, 50%) or without (control, n  = 20, 50%) the need for preoperative ECLS as a bridge to long‐term device from March 2007 to May 2015 at our institution. Demographics and preoperative baseline characteristics as well as early and long‐term outcomes including mortality and complication rates were retrospectively compared between the two groups. There were no statistically significant differences in terms of demographics and most preoperative clinical characteristics. The mean age in the ECLS (CS group) and control group was 43.5 ± 19.4 and 41.3 ± 16.4 ( P  = 0.705), whereas 20 and 25% of patients were females ( P  = 1.000). However, patients from the ECLS group had preoperatively higher lactate ( P  = 0.037), aspartate aminotransferase ( P  < 0.001), and alanine aminotransferase ( P  < 0.001) levels, all of them significantly decreased after surgery ( P   = 0.004, P  = 0.017, and P  = 0.001, respectively) and did not show any statistical differences to the corresponding values from the control group ( P  = 0.597, P  = 0.491, and P  = 0.339, respectively). Postoperatively, patients from the control and ECLS groups had statistically similar incidences of liver failure (30 vs. 35%, P  = 0.736), renal failure (45 vs. 70%, P  = 0.110), need for reopening (35 vs. 60%, P  = 0.113), major cerebrovascular events (35 vs. 30%, P  = 0.736), sepsis (10 vs. 25%, P  = 0.407), wound infection (20 vs. 30%, P  = 0.716), abdominal ischemia requiring surgery (28.6 vs. 36.8%, P  = 0.719), and acute respiratory distress syndrome (25 vs. 35.3%, P  = 1.000). The proportion of patients who were bridged to transplantation was statistically similar between the ECLS and the control groups (40 vs. 52.6%, P  = 0.429). Furthermore, there were no statistically significant differences in terms of early (Breslow [generalized Wilcoxon] P  = 0.907) and long‐term (log‐rank [Mantel–Cox] P  = 0.787) overall cumulative survival accounting for 30‐day survival of 75 versus 75%, 6‐month survival of 60 versus 55%, 1‐year survival of 54 versus 40%, and 7‐year survial of 47 versus 40% in the control and ECLS groups, respectively. ECLS in critical CS as a bridge to implantation of the Berlin Heart Excor ventricular assist device is safe and is associated with improvement in end‐organ function leading to similar excellent early and long‐term survival and incidences of major complications as in patients without the need for preoperative ECLS support.